The diet of young Neandertals from France, Pech de l’Azé I and Hortus II, reconstructed using dental microwear texture analysis - Frank L’Engle Williams; Christopher W Schmidt; Jessica L Droke; Whitney M Karriger; Gaël Becam; Fred H Smith; Marie-Antoinette de Lumley (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Neandertal adults show differences in diet with respect to paleohabitat. To examine whether Neandertal children of France during Marine Isotope Stage 3 also show these dietary distinctions, the deciduous second molars of Pech de l’Azé I, from a cold-temperate period, and Hortus II from Sub-Phase Vb, an extreme cold-arid interval, were examined using dental microwear texture analysis. The comparative sample (n=76) includes deciduous molars from Neolithic forager-farmers of Belgium, including Caverne de la Cave at Maurenne (n=5), Sclaigneaux (n=7) and Bois Madame (n=6), Roman-era farmers from Herculaneum (n=15) and Medieval agriculturalists from Canterbury, England (n=43). When complexity is compared to anisotropy, Pech de l’Azé I exhibits an elevated value from the mastication of plants with hard parts or adherent particles, or the consumption of foods that were poorly processed or grit-laden, whereas Hortus II presents a low value, perhaps from limited access to hard plant parts such as seeds and nuts. However, Pech de l’Azé I and Hortus II resemble each other in having a low value for anisotropy, which is indicative of complicated movements of the jaws during mastication and are dissimilar to Neolithic, Roman and Medieval human children who tend to have higher values. The diets of Neandertal children differ with respect to paleohabitat and typically were more diverse than those of food producers regardless of whether they inhabited wooded or open environments.